Comparison of Aesthetic Ideas in Chinese and Japanese Gardens from the Aesthetics of Mono-no-aware in The tale of Genji - Wang, Jianfeng (Transactions on Social Science, Education and Humanities Research, 2024)
Chinese and Japanese gardens are in a continuous line, but due to regional cultural differences between the two countries, Japanese gardens have formed their own unique aesthetic designs that are different from Chinese gardens. Starting from the Aesthetics of mono-no-aware in The tale of Genji, this article compares and analyzes the aesthetic characteristics of Chinese and Japanese gardens, corresponding to the human beauty, material beauty, and emotional beauty reflected in the "mono-no-aware" view, and interprets the characteristics and origin in the humanistic aesthetics, scenic elements, and emotional connotations between the two. Aiming to correctly grasp the inherent correlation and comparison of Chinese and Japanese garden design ideas through a new perspective of "mono-no-aware" aesthetics.